2017
DOI: 10.1089/hum.2017.016
|View full text |Cite
|
Sign up to set email alerts
|

Gene Delivery of Activated Factor VII Using Alternative Adeno-Associated Virus Serotype Improves Hemostasis in Hemophiliac Mice with FVIII Inhibitors and Adeno-Associated Virus Neutralizing Antibodies

Abstract: While therapeutic expression of coagulation factors from adeno-associated virus (AAV) vectors has been successfully achieved in patients with hemophilia, neutralizing antibodies to the vector and inhibitory antibodies to the transgene severely limit efficacy. Indeed, approximately 40% of mice transduced with human factor VIII using the AAV8 serotype developed inhibitory antibodies to factor VIII (FVIII inhibitor), as well as extremely high titers (≥1:500) of neutralizing antibodies to AAV8. To correct hemophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…HEK293 cells and Huh7 cells were maintained at 37°C in 5% CO 2 in DMEM (Mediatech, Manassas, VA, USA) with 10% fetal bovine serum (Thermo Fisher Scientific) and 1% penicillin-streptomycin (Corning, distributed by Mediatech, Manassas, VA, USA). The hFVIII expression cassette with a synthesized poly A 48 was kindly provided by St. Jude Children’s Research Hospital and flanked by AAV2 inverted terminal repeats (ITRs), in which hFVIII was driven by the liver-specific promoter HLP. The firefly luciferase gene in the AAV cassette with bovine growth factor poly A was driven by the chicken β-actin promoter.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…HEK293 cells and Huh7 cells were maintained at 37°C in 5% CO 2 in DMEM (Mediatech, Manassas, VA, USA) with 10% fetal bovine serum (Thermo Fisher Scientific) and 1% penicillin-streptomycin (Corning, distributed by Mediatech, Manassas, VA, USA). The hFVIII expression cassette with a synthesized poly A 48 was kindly provided by St. Jude Children’s Research Hospital and flanked by AAV2 inverted terminal repeats (ITRs), in which hFVIII was driven by the liver-specific promoter HLP. The firefly luciferase gene in the AAV cassette with bovine growth factor poly A was driven by the chicken β-actin promoter.…”
Section: Methodsmentioning
confidence: 99%
“…Inhibition of AAV8 transduction by NAbs was assessed in vitro according to published methods as described. 48 , 50 Briefly, Huh7 cells were seeded in a 48-well plate at 1 × 10 5 cells/well, and they were cultured with 1 × 10 8 particles AAV8/luciferase that had been pre-incubated with a serial dilution of dog sera from dogs U10 and U11 for 2 hr at 4°C. First, we used a 10-fold dilution with the start concentration of undiluted sera to obtain the NAb range.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…With AAV antibodies persisting for many years after treatment [14], this might preclude the use of the same vector again or even different serotypes due to cross reactivity. Early pre-clinical data, however, has suggested that it may be possible to redose using alternative serotypes with low cross-reactivity [26,27] or rechallenge with the same serotype in combination with a proteasome inhibitor where antibodies are no longer detectable [28]. Although these finding are encouraging, this is an area that warrants considerable further research.…”
Section: Future Challengesmentioning
confidence: 99%